Can village fund improve community welfare in central java province? - Lely Ratwianingsih; Selfia Bintariningtyas; Tri Mulyaningsih (FORUM EKONOMI, 2021)
Village fund is state budget allocated to all villages in Indonesia. This fund is used to finance rural administrative government, rural development, rural empowerment and community development. One of the Village Fund Allocation’s (Alokasi Dana Desa/ADD’s) goals is to reduce poverty and inequality as well as to improve community welfare. Poverty alleviation is a global action under the Sustainable Development Goals (SDGs). This research is aimed to analyze the impact of Village Funds on community welfare by employing the intervening variable poverty levels in Central Java Province. Secondary data from 29 districts in Central Java were used in this research. This was a quantitative research which employed Path Analysis Method. The independent variable in this research was Village Fund and the dependent variable was community welfare which utilized poverty as the intervening variable. Based on the Path Analysis Method, this research found that Village Fund had no impact on community welfare in Central Java province. However, through indirect path analysis, it was found that Village Fund had an impact on community welfare in terms of poverty level. This finding showed that Village Fund had a direct impact on reducing poverty level, and the poverty level affected the community welfare in Central Java accordingly.